Thermal stability and deformability of annealed nanotwinned Al/Ti multilayers. (September 2020) - Zhang, Y.F.; Su, R.; Niu, T.J.; Richter, N.A.; Xue, S.; Li, Q.; Ding, Jie; Yang, Bo; Wang, H.; Zhang, X.
Abstract: Recent studies showed that nanotwinned Al/Ti multilayers have outstanding mechanical properties at room temperature. However, the thermal stability of these multilayers remains unclear. Here, we show that after annealing at 400 °C, nanotwinned Al/Ti multilayers demonstrate excellent thermal stability and limited intermixing when individual layer thickness exceeds 22 nm. Whereas nanolayers of TiAl formed in the annealed Al/Ti 4.5 nm multilayer. Annealing induced substantial hardening, and the magnitude of hardening is greater at smaller layer thickness. In situ micropillar compression tests show the annealed Al/Ti multilayers have high flow stress (exceeding 3 GPa), work hardening capability, and good deformability. Graphical abstract: Image, graphical abstract